Sustainable Development Goals in Local Level Budget and Programs: A Critical Analysis in the Context of Nepal - Sapkota, Sandip (Prashasan: The Nepalese Journal of Public Administration, 2024)
This study critically examines the integration of Sustainable Development Goals (SDGs) into local-level budgets and programs in Nepal, focusing on the alignment of local governance structures with global sustainable development objectives. The study aims to assess the extent of SDG implementation at the grassroots level, identify key challenges, and explore opportunities for enhancing SDG localization in Nepal’s federal governance system. Using a mixed-methods approach, the study combines document analysis with case studies from various local governments. It evaluates the progress and effectiveness of SDG integration, particularly in the post-COVID period, analyzing the institutional learning from the first phase of federal governance (2017–2022) to the present phase. Findings reveal varying degrees of SDG integration across different local governments. Key challenges include limited awareness, inadequate financial resources, and weak institutional capacity, which hinder effective SDG implementation. However, opportunities exist in enhancing budgetary frameworks, capacity-building initiatives, and fostering multi-stakeholder partnerships to strengthen SDG localization. The study has significant policy implications, providing a framework for improving budget allocation, institutional strengthening, and participatory governance to advance sustainable development at the local level. The recommendations serve as a guide for policymakers, local government officials, and development practitioners to effectively incorporate SDGs into planning and budgeting processes, contributing to Nepal’s sustainable and inclusive growth.